Antagonistic activities of volatiles produced by two Bacillus strains against Monilinia fructicola in peach fruit. (22nd June 2018) - Liu, Chang; Yin, Xiaohui; Wang, Qingguo; Peng, Yong; Ma, Yurong; Liu, Pei; Shi, Jingying
Abstract: BACKGROUND: Brown rot caused by Monilinia fructicola is one of most serious diseases of postharvest peach fruit. The objective of this study was to select effective antagonistic bacteria against Monilinia fructicola and evaluate the effects of these strains against brown rot. RESULTS: Four bacterial strains producing inhibitory volatile gas against Monilinia fructicola were isolated from the peach rhizosphere soil. The volatiles produced by 12a ( Bacillus vallismortis ) and 14b ( Bacillus altitudinis ) showed considerable antagonistic activities. Monilinia fructicola showed 80.3% and 68.4% mycelial growth inhibition and cell damage in the presence of strains 12a and 14b, respectively. The inhibition rate of brown rot in peach fruit fumigated with the culture solution of 12a or 14b reached 77.1% and 50.0%, respectively. The volatile compounds produced by 12a and 14b were identified according to gas chromatographic–mass spectrometric analysis. Among them, 6‐methyl‐2‐heptanone and 2‐pentylfuran completely inhibited mycelial growth at 100 µL L −1 concentration. Cedrol showed strong inhibitory activity against mycelial growth at 100 µg L −1 and isodecyl methacrylate inhibited growth at high concentration. The inhibition rate of the 50 µL L −1 artificial mixture of these four volatiles was 59.3% in vitro . CONCLUSION: These results indicate that the two antagonistic bacteria and some volatiles produced by them have potential value in controlling brown rot in harvested peach fruit. © 2018 Society of Chemical Industry